INFLUENCE OF PHYSICOCHEMICAL PARAMETERS ON ARTEMIA POPULATION IN SOLAR SALTPANS OF KANYAKUMARI DISTRICT, TAMILNADU, INDIA - Y., Biju; M. , Krishnaveni; M. , Michael Babu; S. , Krishnakumar (International Journal of Psychosocial Rehabilitation, 2020)
Artemia, commonly known as brine shrimp, are unique inhabitants of hypersaline environments. The objective of the study is to evaluate physicochemical parameters and the population of Artemia in two selected hypersaline ecosystems of Kanyakumari district. To better understand the growth of Artemia, different physicochemical parameters, including temperature, pH, salinity, dissolved oxygen, and depth of water, were examined from May 2018 to April 2019. The influence of physicochemical parameters on Artemia population in different seasons of a saltpan ecosystem of reservoir, condenser, and crystallizer ponds at both stations was studied. The highest temperature was recorded (31.72 oC) in the crystallizer pond and pH (8.7) in the condenser pond during postmonsoon seasons at both stations. The highest salinity was reported (157.175 ppt) from crystallizer ponds during the premonsoon at both study sites. In case of DO (5.317) and water depth (71.73) was reported maximum in reservoir pond at both stations during monsoon seasons. The different stages of Artemia populations were recorded during postmonsoon season on both saltpans. The highest Artemia population (14.1) was reported from reservoir ponds at both stations during the postmonsoon season. Parameters such as temperatures, pH, salinity, dissolved oxygen, and depth of water extensively influenced the abundance of Artemia population in the crystallizer ponds of both study stations. Artemia population was significant (p > 0.05) in postmonsoon seasons and sampling units at station 2. The various stages of the Artemia population were non-significant (p > 0.05) in seasons and sampling sites at both study areas. The abundance of Artemia population was high at station 2 from reservoir pond during the postmonsoon season